Hubungan Kualitas Layanan Pendidikan Gratis Terhadap Kepuasan Siswa Sekolah Menengah Pertama Negeri (SMPN) Di Wilayah Kecamatan Tambun Selatan - ., Syahyono (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
This study aims to analyze the relationship of quality of free education service to the satisfaction of junior high school students of the country (SMPN) in the area of ​​South Tambun District. The variables in this research are Tangible, Reliability, responsiveness, Assurance and Emphaty, as independent variable and Customer Satisfaction as dependent variable. This research has been done by distributing questionnaires to 100 respondents students of class VII and class VIII through judgmental sampling technique. The analysis technique used is quantitative analysis technique with SPSS method. The results of this study showed that Tangible, Reliability, responsiveness, Assurance and Emphaty have a positive and significant impact on customer satisfaction